IMPROVEMENT OF PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF COMMUNICATIVE CULTURE IN FUTURE HIGHER EDUCATION SPECIALISTS - Sitorabegim Djamolitdinovna, Mukhamedjanova (International Journal of Psychosocial Rehabilitation, 2020)
The article substantiates the possibility of improving the quality of professional training of future specialists in vocational educational institutions by forming their communicative culture in the conditions of innovative educational activity.